Obesonomics - Sanjay Kalra; Madhur Verma; Lakshmi Nagendra; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
Economic and commercial determinants of health, as wellas health- related determinants of economy, are graduallybeing understood by researchers and public healthspecialists. One condition which is influenced by economicfactors, and which also impacts economic health, is obesity.In this opinion piece, we conceptualize obesonomics as thebidirectional relationship between obesity and economichealth. We explore the scope and spectrum ofobesonomics, and utilize it to suggest a pragmaticframework for mitigation of obesity as well as its associatedfinancial factors. Keywords: Commercial determinants, economicdeterminants, health economics, medical anthropology,medical sociology, obesity, overweight.